2021
DOI: 10.1097/scs.0000000000007965
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of the Effect of Weight Loss on Eustachian Tube Function by Transnasal Videoendoscopy

Abstract: Objective: To investigate the effect of weight loss after bariatric surgery on eustachian tube (ET) function with video endoscopy. Materials and Methods: The present study was conducted as a prospective cohort and was completed with 19 patients. Three-step tympanometry (basal, Toynbee, Valsalva), dynamic slow-motion video endoscopy, and the Eustachian Tube Dysfunction Questionnaire-7 (ETDA-7) were applied to the patients preoperatively before bariatric surgery and in the postoperative 6th month. Dynamic slow-m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 16 publications
0
2
0
Order By: Relevance
“…The findings of the study indicated that for the majority of patients, rapid weight loss resulting from bariatric surgery led to improvements in both DSVE imaging and the symptoms associated with ET dysfunction. However, in certain individuals, this weight loss could result in PET [ 16 ]. Eighty patients were evaluated in a recent study that revealed that 18.75% of those who underwent bariatric surgery had PET symptoms.…”
Section: Discussionmentioning
confidence: 99%
“…The findings of the study indicated that for the majority of patients, rapid weight loss resulting from bariatric surgery led to improvements in both DSVE imaging and the symptoms associated with ET dysfunction. However, in certain individuals, this weight loss could result in PET [ 16 ]. Eighty patients were evaluated in a recent study that revealed that 18.75% of those who underwent bariatric surgery had PET symptoms.…”
Section: Discussionmentioning
confidence: 99%
“…The DSVE findings add another layer of diagnostic precision where clinicians can glean valuable preoperative insights into ETD with other nasal and nasopharyngeal pathologies in one setting when combined with diagnostic nasal endoscopy [ 8 ]. This synergistic approach enhances the overall assessment and helps in assessing the effects of interventions on ET function; DSVE enables clinicians to monitor treatment progress and tailor patient management strategies accordingly [ 11 ]. This capability for longitudinal assessment contributes to more effective patient care and improved treatment outcomes.…”
Section: Reviewmentioning
confidence: 99%